2018
DOI: 10.1021/acs.iecr.8b04498
|View full text |Cite
|
Sign up to set email alerts
|

Single and Binary Mixture Adsorption Behaviors of C6–C8 Hydrocarbons on Silica–Alumina Gel

Abstract: To ensure the technical use of natural gas, heavy hydrocarbons and other components must be separated. Therefore, in this work the adsorption of C 6 −C 8 hydrocarbons n-hexane, n-heptane, n-octane, benzene, toluene, and cyclohexane on a commercial silica−alumina gel (Sorbead H) was investigated in experiments and dynamic simulations. Single and binary mixture equilibrium isotherms were determined from cumulative breakthrough curve experiments on a fixed bed adsorber at 25−75 °C and 1.3 bar (abs) in the trace r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 51 publications
0
5
0
Order By: Relevance
“…We assume thermodynamic equilibrium when the outlet concentration reaches the concentration at the inlet of the adsorber. In a cumulative procedure, subsequent equilibrium points can be measured by increasing the concentration of the adsorptive step by step …”
Section: Methodsmentioning
confidence: 99%
“…We assume thermodynamic equilibrium when the outlet concentration reaches the concentration at the inlet of the adsorber. In a cumulative procedure, subsequent equilibrium points can be measured by increasing the concentration of the adsorptive step by step …”
Section: Methodsmentioning
confidence: 99%
“…The effective mass transfer coefficient can be calculated as follows: , where D eff,hetero is the effective diffusion coefficient [m 2 s –1 ]; R p is the particle radius of equivalent sphere [m]; ρ p is the average density of particle [kg m –3 ]; ε p is the particle porosity [−]; and β Film is the film transport coefficient [m s –1 ].…”
Section: Physical Modelmentioning
confidence: 99%
“…In single-component adsorption with purely physical interactions, two mass balances for the solid and the fluid phase have to be solved. For a detailed derivation of the balances and differential equations, please refer to refs and . All parameters used can be either calculated physically or estimated with sufficient accuracy.…”
Section: Physical Modelmentioning
confidence: 99%
“…However, recent research has shown that mesoporous silicas such as MCM-41 are very efficient scavengers of larger VOCs like MAHC when compared with industrial standards such as Tenax™ TA [18,23]. Aromatic molecules such as benzene and toluene have shown strong interactions with silica surfaces [24] and with the ability to tune textural properties of porous silicas, VOC adsorption can be improved [25]. Furthermore, silicas can be readily tailored by chemical modification to target specific VOCs or conditions.…”
Section: Introductionmentioning
confidence: 99%